Odpowiedź :
Odpowiedź:
a) -17x-9
b) 64x -6
c) 12x-18
d) 25x-11
a) 9x - 4 = 8x + 5 L = 9x - 8x P = 4 + 5 x = 9 spr. 9 · 9 - 4 = 8 · 9 + 5 81 - 4 = 72 + 5 77 = 77
b) 5x - 6 (x - 7) = 8x - 9 (10 + x) 5x - 6x + 42 = 8x - 90 - 9x L = 5x - 6x - 8x + 9x P = -42 - 90 nie ma rozwiązania
c) 5x - 9 + x = 3 (2x - 3) 5x - 9 + x = 6x - 9 L = 5x + x - 6x P = 9 - 9 0 = 0
d) 4 (3x - 2) + 5 = 2 (6x - 4) + x 12x - 8 + 5 = 12x - 8 + x L = 12x - 12x - x P = 8 - 5 - 8 -x = -5 spr. 4 (3 - 5 - 2) + 5 = 2 (6 - 5 - 4) - 5